Naturalizm bez normatywności? Głos w obronie epistemologii znaturalizowanej - Trybulec, Barbara (Filozofia Nauki, 2008)
The topic of the paper is to be the problem of normativity within naturalised epistemology. I pose a question whether naturalism can be conducted as a normative enterprise or whether it is merely descriptive as traditional epistemologists and some naturalists maintain. The article consists of two parts. The first one is an introduction to the main theses of naturalised epistemology, and the second one presents and disputes arguments against naturalised epistemology introduced in Jonathan Knowles’ book Norms, Naturalism and Normativity. In the first part of the paper I indicate main differences between traditional and naturalised epistemology, especially I analyse their answers to the most important epistemological questions: What is the source of epistemic norms? When are beliefs valuable and how to gain such beliefs? What are criteria of justified belief and knowledge? The reason of differences in solutions of these problems is rotted in a different attitude to the naturalistic fallacy taken by the two sides of the discussion. Naturalists treat this fallacy as something that cannot be avoided and this approach deeply influences their account of normativity. To justify this thesis I firstly recall the traditional meaning of “normativity” on the bases of Descartes’ epistemology, post-Cartesian internalists’ and neopositivits’ works. Secondly, I present how and why the meanings of “epistemic norm” and “justified belief” have changed within naturalism. In this part I refer to Quine’s and Goldman’s naturalism. The second part of the paper discuses Knowles’ argument that the task of delivering genuine epistemic norms by naturalism is misguided and unreachable, for norms which naturalists refer to are reducible to descriptive statements. Naturalism, therefore, cannot be normative and consequently it cannot be an epistemology. I do not agree with this statement and in the last part of the paper I present how naturalised epistemic norms could be understood as different from descriptive statements, what functions they could perform and why naturalised epistemology is not redundant.